Laporan Kasus: Hemangioma Lingual pada Bayi Baru Lahir - Fairuz Niken Prasasti; Elsye Souvriyanti; Sri Hastuti Andayani (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Hemangioma is the most common benign vascular tumor in infancy and is generally characterized by a proliferative phase followed by spontaneous involution. Although most cases resolve without intervention, treatment is required when hemangiomas cause functional impairment, ulceration, or life-threatening complications. Lingual hemangioma is a rare presentation and may result in significant feeding difficulties and airway compromise, requiring prompt and multidisciplinary management. This study aims to report the comprehensive management of a refractory lingual hemangioma in an infant, emphasizing diagnostic evaluation, therapeutic strategy, and nutritional support. A six-month-old female infant presented with a lingual hemangioma associated with progressive feeding difficulties. Prior to initiating therapy, a thorough diagnostic workup was performed, including echocardiography to assess cardiac function, magnetic resonance imaging (MRI) to evaluate lesion extent, and computed tomography angiography (CT-angiography) to delineate vascular anatomy. The patient initially received oral propranolol as first-line therapy; however, due to an inadequate response, combination chemotherapy with Bleomycin–Vincristine (BV) was initiated. To minimize the risk of toxicity, a 50% dose reduction was applied. Clinical evaluation demonstrated a favorable therapeutic response, with a reduction in lesion size and improvement in feeding ability after 10 weeks of treatment. No severe adverse effects were observed during the treatment period. To ensure adequate nutritional intake and support growth, enteral nutrition via a nasogastric tube (NGT) was provided throughout the course of therapy. This case highlights the importance of comprehensive diagnostic assessment, individualized treatment planning, and close monitoring in refractory hemangioma. In addition, optimal nutritional support plays a crucial role in overall patient outcomes. A multidisciplinary approach is essential for the successful management of complex infantile hemangiomas with functional complications.